Session 1, Panel 1, Weir, Liz. Storytelling, Peace and Conflict Resolution - Liz Weir - Jarvis, Dale (2010)
Liz Weir speaking at the 18th Annual Conference of Storytellers of Canada-Conteurs du Canada.